Exploring self-efficacy among preservice English teachers in southeast Mexico - Patricia Núñez-Mercado; Oscar Manuel Narváez-Trejo; Gabriela Guadalupe Estrada-Sánchez (Universitas Syiah Kuala, 2026)
Teachers’ self-efficacy is strongly associated with highly positive student outcomes. While research highlights the malleability of teachers’ self-efficacy beliefs during initial training and early career stages, a significant gap exists in understanding this construct within the specific context of Mexican English teacher education programs. This mixed-methods sequential design case study addresses this gap by looking into the self-efficacy beliefs of EFL preservice teachers enrolled in three teacher education programs at a public university in southeastern Mexico. For the quantitative stage, 71 preservice teachers answered the Teacher Sense of Self-Efficacy Scale. For the qualitative stage, semi-structured interviews were conducted with two purposively selected students from each program to gain deeper insights into the rationales underpinning their self-efficacy perceptions. Quantitative data were analyzed using descriptive statistics, and qualitative data using thematic analysis. The findings corroborate a higher sense of self-efficacy in instructional strategies (=4.0) and the lowest in classroom management, with disruptive behavior items scoring as low as 2.72. Student engagement was moderately high, particularly in fostering learners’ self-confidence (4.32). Qualitative data echoed this pattern: preservice teachers with more extensive teaching practice reported greater confidence, while those with limited experience struggled most. Furthermore, a more critical and reflective attitude towards their own capabilities was revealed among those actively pursuing further professional development. The results draw Mexican teacher education programs’ attention to prioritizing teaching practice experience, strengthening instruction in classroom management strategies, fostering collaborative learning opportunities, and reinforcing language proficiency. The present study provides valuable empirical evidence to inform curriculum design and pedagogical approaches that can enhance the quality of language education in the region.